(untitled) (LETRAS, 2006)
Describe y analiza los temas y procedimientos discursivos de siete extensos poemas de Eunice Odio, y se detiene en dos aspectos: lo sexual en cuanto asociado al cuerpo como objeto poético, y la condición de la conciencia existencial en la naturaleza; así, el discurso erótico en la poesía pasa a ser un proceso de trasgresión. Odio experimenta con tópicos, con alusiones intertextuales y con temas recurrentes que apartan su obra poética de la poesía convencional amorosa, y la muestran como una notable manifestación vanguardista. This article describes and analyzes the discourse techniques of seven long poems by Eunice Odio, and emphasizes two particular aspects: sexuality and its relation with the body as a poetic object, and the condition of existential awareness in nature. Thus the erotic discourse in this poetry becomes a process of transgression. Odio experiments with topics, intertextual allusions and recurring themes which set her poems apart from conventional love poetry, and identify her with an outstanding avant-guard perspective.